PENGAMBILAN FOTO COPI MINUTA AKTA DAN PEMANGGILAN NOTARIS - Djoko Sukisno (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The main problem of this paper is what can be used as limitation of Majelis Pengawas Daerah Notaris in implementing Article 66 Regulation Number 30 in the year of 2004 about Notaris Position especially in civil court ? The conclusion of this paper is the answer of the problem. The agreement given to the judge to take photocopy of the deed if there is not copy of the deed of there is a doubt toward the copy of the deed, and the agreement to call Notary by the judge can be given if it is related to official certificate ; the material of the certificate still needs witness form Notary as expert witness or Notary plays as the defender.